Open-Access Textbooks and Financial Sustainability: A Case Study on Flat World Knowledge - Hilton III, John; Wiley, David (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
Many college students and their families are concerned about the high costs of textbooks. A company called Flat World Knowledge both gives away and sells open-source textbooks in a way it believes to be financially sustainable. This article reports on the financial sustainability of the Flat World Knowledge open-source textbook model after one year of operation.